A grammar for a text based music scoring program - Kay, P. (Massey University, 2006)
The grammar for a text-based music scoring software package and a short example is presented. The computer program developed using this language (available from the author's website) will form the basis for future research into a variety of different input methods for creating music scores.
Keywords: Music scoring software; Computer programming